Hubungan Pengetahuan dan Sikap Perawat Terhadap Pelaksanaan Pendokumentasian Edukasi Kesehatan di Ruangan Irna Surgical - Fadhila Putri; Susi Erianti; Asfeni Asfeni (Jurnal Ners, 2025)
Incomplete documentation of health education as well as lack of information about the patient's condition have a negative impact on the key performance indicator (KPI) score, which is an assessment of nurse performance in the hospital. Those situations can also cause anxiety and worry in patients. This study aims to determine the relationship between nurses' knowledge and attitude with the implementation of health education documentation at Arifin Achmad Regional Hospital of Riau Province. This study used a correlation design with a cross-sectional approach, involving 57 samples selected using the Consecutive Sampling technique. The instruments of this study were questionnaires and observation sheets. The data obtained were then analyzed using the chi-square test. The results showed that there was a relationship between nurses' attitudes and the implementation of health education documentation with a p-value of 0.000. On the other hand, the results showed that there was no relationship between nurses' knowledge and the implementation of health education documentation, with a p-value of 0.064. It can be concluded that nurses' attitudes are one of many factors, namely motivation, skills, and psychology, that influence the implementation of health education documentation in surgical inpatient installations. Nurses are expected to be knowledgeable about health education documentation and show a proper attitude while implementing it..Keywords: Knowledge, Attitudes And Educational Documentation.